Body composition patterns among type 2 diabetes mellitus patients versus nondiabetic adults in Saudi Arabia - Alfadhli, Eman; Darandari, Ishraq; Altaweel, Maha; Alharbi, Sara; Jadw, Asma; Aljohani, Ghadi; Mohammad, Sarah (Frontiers in Endocrinology, 2025)
ObjectivesTo explore differences in body composition between individuals with type 2 diabetes mellitus (T2DM) and those without diabetes in Medina, Saudi Arabia, stratified by sex and age.MethodsA cross-sectional study was conducted at Taibah University, four primary care centers, and diabetes center in Medina, Saudi Arabia, from July to September 2023, involving 630 adults with and without T2DM. Body composition was assessed using a bioelectrical impedance analysis (BIA), measuring weight, body mass index (BMI), total body fat, visceral fat (VF), muscle mass, and bone mass. Participants were grouped into three categories: young age (18–40 years), middle age (41–60 years), and older age (>60 years). Body composition differences between groups were analyzed using independent t-tests.ResultsOf the 630 participants, 42.4% had T2DM. Among young women with T2DM, BMI, total body fat, VF, muscle mass, and bone mass were significantly higher (p < 0.001) compared to women without diabetes. However, their muscle and bone mass percentages were lower. In contrast, no significant differences were found between middle-aged women with and without T2DM. Among older women, those with T2DM had significantly higher BMI (p = 0.030) and VF (p = 0.007). For men, body composition differences were mostly non-significant across age groups, except for lower muscle mass percentage in young men with T2DM (p = 0.013).ConclusionSex- and age-specific differences in body composition exist between adults with and without T2DM. These findings highlight the importance of tailored strategies in T2DM prevention and management. Future research should examine underlying mechanisms and evaluate the impact of targeted interventions.